Neurological aspects of menopause - influence of initiating hormone replacement therapy. II. Neuropathic disorders - M. Kanadys, Wiesław (Menopause Review/Przegląd Menopauzalny, 2003)
Menopause as well as hormone replacement therapy (HRT) may influence the course of diseases, which arised from dysfunction or primary damage in the central nervous system. During menopause great changeability of migraine headache is observed, and exacerbated migraine is associated with intensity of climacteric vasomotor symptoms. HRT may exacerbate migraine, although most women tolerate this treatment well. Frequency and severity of tension-type headache did not change significantly during menopause and as an effect of HRT. In women with epilepsy varying effects of menopause, as well as HRT on seizure activity were noted. Sleep disturbance, especially insomnia, increases in postmenopausal women. Initiating HRT significantly improves subjective sleep quality, while it has only a slight effect on both objective sleep quality (psychometry) and sleep architecture (polysomnographic study).